Fungal bioaugmentation of anaerobic digesters fed with lignocellulosic biomass: What to expect from anaerobic fungus Orpinomyces sp. (April 2019) - Akyol, Çağrı; Ince, Orhan; Bozan, Mahir; Ozbayram, E. Gozde; Ince, Bahar
Graphical abstract: Highlights: Fungal bioaugmentation with Orpinomyces sp. increased the methane yield by 15–33%. Harvesting stage of the crops greatly influenced the process performance. Microbial groups were clustered based on bioaugmentation and crop material. Anaerobaculum was only enriched in the bioaugmented digesters. Methanogenic archaeal diversity was not affected by fungal bioaugmentation. Abstract: Energy-efficient biogas reactors are often designed and operated mimicking natural microbial ecosystems such as the digestive tracts of ruminants. Anaerobic fungi play a crucial role in the degradation of lignocellulose-rich fiber thanks to their high cellulolytic activity. Fungal bioaugmentation is therefore at the heart of our understanding of enhancing anaerobic digestion (AD). The efficiency of bioaugmentation with anaerobic fungus Orpinomyces sp. was evaluated in lignocellulose-based AD configurations. Fungal bioaugmentation increased the methane yield by 15–33% during anaerobic co-digestion of cow manure and selected cereal crops/straws. Harvesting stage of the crops was a decisive parameter to influence methane production together with fungal bioaugmentation. A more efficient fermentation process in the bioaugmented digesters was distinguished by relatively-higher abundance of Synergistetes, which was mainly represented by the genus Anaerobaculum . On the contrary, the composition of the methanogenic archaea did not change, and the majority of methanogens was assigned to Methanosarcina .